Growth and feeding of juvenile cod (Gadus morhua L.) - Hawkins, A. D.; Soofiani, N. M.; Smith, G. W. (ICES Journal of Marine Science, 1985)
Growth and feeding of immature cod were investigated in Upper Loch Torridon (57°33'N 5°36'W), a fjordic sea loch on the west coast of Scotland. Growth was estimated from mean length and weight at age, and also from the changes in length of tagged fish. Feeding rates were measured by two independent methods: 1) laboratory measurements of the ration levels necessary to produce growth rates similar to those observed in the wild (measured from mean length at age), and 2) examination of the stomach contents of wild fish, by the application of experimentally measured elimination coefficients. Growth rates measured from mean length at age were lower than those measured from tagged fish, perhaps because faster-growing fish leave the loch, biasing mean length at age downwards. There were strong seasonal differences in the growth and condition factor of the cod, both being highest in summer and autumn and lower during winter and spring. The feeding rates estimated by the two independent methods were similar, though those estimated from growth rates were generally lower, probably reflecting an underestimation of growth rate and also differences in the diet and activity levels of laboratory and wild fish. It is suggested that the poor condition and lower food intake of fish in the winter result from a lack of vulnerable prey organisms, rather than any drop in growth efficiency at lower temperatures. The production of juvenile cod in Scottish sea lochs may well be limited by the winter food supply.